2009
DOI: 10.3181/0811-mr-318
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury:Apoptosis and Signaling Mechanisms

Abstract: Acute lung injury (ALI) has been documented clinically following several pathological states such as trauma, septic shock and pneumonia. The histopathological characteristics, paired with the production of a number of cellular pro-inflammatory mediators, play a crucial role in the progression of ALI. During ALI, polymorphonuclear neutrophil (PMN)-mediated apoptosis is delayed by macrophages, possibly via effects on the Fas/FasL mediated pathway, leading to the accumulation of these cells at the site of injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 114 publications
(113 reference statements)
5
99
1
7
Order By: Relevance
“…Previous studies have tested the hypothesis that an increased duration of sepsis stimulates apoptosis in lung tissue, 44,45 whereas others have suggested a biphasic response where changes in Bax/Bcl-2 protein levels were found after sepsis onset. 40 Although NF-κB could have a role in apoptosis by regulating the expression of genes involved in cell death, a specific role of NF-κB on the apoptotic process cannot be ascertained from our data. As reported by several investigators, apoptosis is a major pathway responsible for the resolution of alveolar cells in ARDS.…”
Section: Inhibition Of Lps-induced Airway Cell Injury Ne Cabrera-benícontrasting
confidence: 49%
See 1 more Smart Citation
“…Previous studies have tested the hypothesis that an increased duration of sepsis stimulates apoptosis in lung tissue, 44,45 whereas others have suggested a biphasic response where changes in Bax/Bcl-2 protein levels were found after sepsis onset. 40 Although NF-κB could have a role in apoptosis by regulating the expression of genes involved in cell death, a specific role of NF-κB on the apoptotic process cannot be ascertained from our data. As reported by several investigators, apoptosis is a major pathway responsible for the resolution of alveolar cells in ARDS.…”
Section: Inhibition Of Lps-induced Airway Cell Injury Ne Cabrera-benícontrasting
confidence: 49%
“…38 The induction of apoptosis-mediated DNA damage is an important characteristic in the development of acute lung injury during sepsis and ARDS. 40,41 Apoptosis occurred in airway epithelial cells after LPS administration in an in vivo rat model. 42 While proliferation of type-II alveolar cells occurs during the early phase of ARDS as a reparative phenomenon, extensive apoptosis is responsible for the loss of these cells in the resolution phase.…”
Section: Inhibition Of Lps-induced Airway Cell Injury Ne Cabrera-benímentioning
confidence: 99%
“…The histopathological features of lung injury in septic mice demonstrated here are resembled in the clinical condition of patients with sepsis (41). Other studies have indicated that apoptosis plays an important role on progression of sepsis (42,43). Oberholzer and colleagues suggested that targeting signaling pathways that lead to apoptosis would represent a new therapeutic target for the patient with sepsis or other related clinical conditions (34).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 81%
“…First, acute blood loss might result in a decreased number of BALF macrophages via migration to the primary site of injury or inadequate supply of precursor monocytes from the peripheral circulation. 37 Second, alveolar macrophages detect and respond to mechanical stress by release of cytokines such as TNF-α, IL-8, and IL-6. 38 Hence, mechanical forces applied during artificial ventilation might be converted into early proinflammatory signals resulting in activation and adhesion of macrophages to the alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%